2008
DOI: 10.1007/s11910-008-0078-y
|View full text |Cite
|
Sign up to set email alerts
|

Update on apraxia

Abstract: Apraxia is classically defined as difficulty performing learned, skilled gestures. In this review, we describe the range of motor impairments classified as apraxia, focusing on ideomotor limb apraxia. We present several prominent models of praxis to explain the variety of difficulties seen in patients with apraxia. We also discuss the large-scale frontal-parietal-basal ganglia network thought to underlie praxis. In this context, we highlight the common occurrence of limb apraxia in corticobasal degeneration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 48 publications
2
70
0
3
Order By: Relevance
“…At the basis of ideational apraxia there would be amnesia for the use of objects, such as a disorder in recalling semantic memory of attributes relating to object use. In conclusion, ideational apraxia might not constitute a higherorder programming deficit of movement per se, but a combination of executive, language, and memory deficits or a diffuse reduction of cognitive resources (Gross and Grossman, 2008). Different lesion sites have been indicated as responsible for ideational apraxia, showing an involvement of mainly left temporo-parieto-occipital regions (Hécaen, 1972;Bolognini et al, 2015) even if patients with ideational apraxia have also been reported following frontal lesions, or basal ganglia damage (De Renzi e Lucchelli, 1988;Manuel et al, 2013;Huey et al, 2009).…”
Section: Introductionmentioning
confidence: 90%
“…At the basis of ideational apraxia there would be amnesia for the use of objects, such as a disorder in recalling semantic memory of attributes relating to object use. In conclusion, ideational apraxia might not constitute a higherorder programming deficit of movement per se, but a combination of executive, language, and memory deficits or a diffuse reduction of cognitive resources (Gross and Grossman, 2008). Different lesion sites have been indicated as responsible for ideational apraxia, showing an involvement of mainly left temporo-parieto-occipital regions (Hécaen, 1972;Bolognini et al, 2015) even if patients with ideational apraxia have also been reported following frontal lesions, or basal ganglia damage (De Renzi e Lucchelli, 1988;Manuel et al, 2013;Huey et al, 2009).…”
Section: Introductionmentioning
confidence: 90%
“…The MCA territory is an important area for motor function because it is comprised of the CST, the corticoreticulospinal tract and neural tracts which are related with apraxia [4,5,6,7,8,9,10,11,12,13,14,15,16]. In addition, the MCA occupies the largest area among the cerebral artery territories and has many branches.…”
Section: Resultsmentioning
confidence: 99%
“…That seems to be related to the characteristics of the MCA territory for motor function. The MCA territory comprises the corticospinal tract (CST) which is mandatory for fine motor activity of hand, the corticoreticulospinal tract which is involved in postural control and locomotor function, the corticofugal fibers which are responsible for limb-kinetic apraxia, and the anterior portion of superior longitudinal fasciculus which is related with ideomotor apraxia [4,5,6,7,8,9,10,11,12,13,14,15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…Those acts might be transitive (i.e. involving tools or multi-step actions, such as sawing a piece of wood or teeth brushing) or intransitive (e.g., pantomime of gestures and imitation tool use) (Gross et al, 2008). These two different subtypes of apraxia are classified separately -conceptual apraxia and ideomotor apraxia respectively, but might coincide together.…”
Section: Apraxia As a Stroke Consequencementioning
confidence: 99%